(64)Cu-Labeled Phosphonate Cross-Bridged Chelator Conjugates of c(RGDyK) for PET/CT Imaging of Osteolytic Bone Metastases - Ocak, Meltem (Cancer Biother Radiopharm, 2018)
Objective: The goal of this research was to evaluate c(RGDyK) conjugated to phosphonate-based cross-bridged chelators using Cu-free click chemistry in the 4T1 mouse mammary tumor bone metastasis model in comparison with (64)Cu-CB-TE2A-c(RGDyK), which previously showed selective binding to integrin αvβ3 on osteoclasts. Experimental: Two phosphonate-based cross-bridged chelators (CB-TE1A1P and CB-TE1K1P) were conjugated to c(RGDyK) through bio-orthogonal strain-promoted alkyne–azide cycloaddition. In vitro and in vivo evaluation of the (64)Cu-labeled TE1A1P-DBCO-c(RGDyK) (AP-c(RGDyK)), TE1K1P-PEG4-DBCO-c(RGDyK) (KP-c(RGDyK)), and CB-TE2A-c(RGDyK) were compared in the 4T1 mouse model of bone metastasis. The affinities of the unconjugated and chelator-c(RGDyK) analogs for αvβ3 integrin were determined using a competitive-binding assay. For in vivo evaluation, BALB/c mice were injected with 1 × 10(5) 4T1/Luc cells in the left ventricle. Formation of metastases was monitored by bioluminescence imaging (BLI) followed by small-animal PET/CT 2 h postinjection of radiotracers. Results: The chelator–peptide conjugates showed similar affinity to integrin αvβ3, in the low nM range. PET imaging demonstrated a higher uptake in bones having metastases for all (64)Cu-labeled c(RGDyK) analogs compared with bones in nontumor-bearing mice. The correlation between uptake of (64)Cu-AP-c(RGDyK) and (64)Cu-KP-c(RGDyK) in bones with metastases based on PET/CT imaging, and osteoclast number based on histomorphometry, was improved over the previously investigated (64)Cu-CB-TE2A-c(RGDyK). Conclusion: These data suggest that the phosphonate chelator conjugates of c(RDGyK) peptides are promising PET tracers suitable for imaging tumor-associated osteoclasts in bone metastases.